Biodegradable and Implantable Triboelectric Nanogenerator Improved by β‐Lactoglobulin Fibrils‐Assisted Flexible PVA Porous Film - Yichang Quan; Engui Wang; Han Ouyang; Lingling Xu; Lu Jiang; Lijing Teng; Jiaxuan Li; Lin Luo; Xujie Wu; Zhu Zeng; Zhou Li; Qiang Zheng (Advanced Science)
Abstract Triboelectric nanogenerators (TENGs) are highly promising as implantable, degradable energy sources and self‐powered sensors. However, the degradable triboelectric materials are often limited in terms of contact electrification and mechanical properties. Here, a bio‐macromolecule‐assisted toughening strategy for PVA aerogel‐based triboelectric materials is proposed. By introducing β‐lactoglobulin fibrils (BF) into the PVA aerogel network, the material's mechanical properties while preserving its swelling resistance is significantly enhanced. Compared to pure PVA porous film, the BF‐PVA porous film exhibits an eightfold increase in fracture strength (from 1.92 to 15.48 J) and a fourfold increase in flexibility (from 10.956 to 39.36 MPa). Additionally, the electrical output of BF‐PVA in triboelectric performance tests increased nearly fivefold (from 45 to 203 V). Leveraging these enhanced properties, a biodegradable TENG (bi‐TENG) for implantable muscle activity sensing is developed, achieving real‐time monitoring of neuromuscular processes. This innovation holds significant potential for advancing implantable medical devices and promoting new applications in bio‐integrated electronics.